2022
DOI: 10.3390/ijerph192013209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8-Week Exhausting Deep Knee Flexion Flywheel Training on Persistent Quadriceps Weakness in Well-Trained Athletes Following Anterior Cruciate Ligament Reconstruction

Abstract: Persistent quadriceps weakness after anterior cruciate ligament (ACL) reconstruction is a common hurdle to efficient rehabilitation. Therefore, we evaluated a new treatment strategy for athletes with ACL reconstruction. Eleven athletes with unilateral ACL reconstruction performed one set of flywheel Bulgarian split squats to exhaustion with a maximum knee extension of 60°, over 16 sessions, on their reconstructed limb. Quadriceps rate of force development (RFD) 0–50 ms (RFD0–50 ms), and 0–150 ms (RFD0–150 ms),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, reported data suggests that, compared to equivolumed eccentric, traditional, or plyometric training, the combination of eccentric and plyometric load was most effective in improving dynamic stability, the Lysholm knee scale, the return to sport index, and hop tests (limb symmetry indexes). The effects of eccentric training (flywheel) on maximal strength, quadriceps rate of force development (RFD), and voluntary activation were examined in 11 collegiate athletes with unilateral ACL reconstruction [ 32 ]. During eight weeks of intervention (2 sessions per week), participants performed one all-out set of Bulgarian squats on the injured leg using a flywheel in addition to regular training practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reported data suggests that, compared to equivolumed eccentric, traditional, or plyometric training, the combination of eccentric and plyometric load was most effective in improving dynamic stability, the Lysholm knee scale, the return to sport index, and hop tests (limb symmetry indexes). The effects of eccentric training (flywheel) on maximal strength, quadriceps rate of force development (RFD), and voluntary activation were examined in 11 collegiate athletes with unilateral ACL reconstruction [ 32 ]. During eight weeks of intervention (2 sessions per week), participants performed one all-out set of Bulgarian squats on the injured leg using a flywheel in addition to regular training practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the eccentric training group was found to yield significantly bigger gains in the Lysholm knee scale in comparison to the control group (traditional rehabilitation training). Recently, one set of eccentric-oriented Bulgarian squats, performed two times per week for eight weeks during late-stage rehabilitation, was found to be a robust tool to improve quadriceps power in well-trained team sport athletes with ACL reconstruction [ 32 ]. Furthermore, study results revealed that strength gains are baseline-dependent, with the stronger the athletes, the smaller the gains over time.…”
Section: Introductionmentioning
confidence: 99%